Über-Blicke : Abstrakt Konkret Informel : Deutsche Kunst nach 1945. - Galerie Neher, Essen (Essen : Galerie Neher, 1991)
Ackermann, Max ; Albers, Josef ; Brüning, Peter ; Buchheister, Carl ; Diens, Rolf-Gunter ; Geiger, Rupprecht ; Hartung, Hans ; Hoehme, Gerhard ; Kricke, Norbert ; Luther, Adolf ; etc.
Über-Blicke : Abstrakt Konkret Informel : Deutsche Kunst nach 1945, Galerie Neher, Essen, 21. September bis 5. November 1991
boek